التوجيهات النبوية في التعامل مع غير المسلمين : الأقلية المسلمة في سريلانكا أنموذجا‏ - إبراهيم، محمد صديق بن محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The study highlights the problems and challenges faced by the Sri Lankan Muslim minority from some of the Buddhist and Hindu extremist movements and organizations. These are organized in a systematic way to fight the Islam intellectually, socially, economically and culturally with the aim of obliterating Islamic identity. The main reason that has increased and exacerbated these problems is the corruption of some Muslims in dealing with non-Muslims. Therefore, the study concentrates on finding the Prophetic guidance in dealing with non-Muslims by presenting some religious and cultural issues in Sri Lankan Muslim minority based on the survey of National Shoora Council of Sri Lanka. The academic nature of the study requires an inductive, a descriptive and historical, and an analytical methodology that yielded a number of important results in examining the history of Sri Lanka, as well as demonstrating the history of Muslims there since the first century of “Hijrah”. Also, the study clarifies the concept of Muslim minority, its initiation, its unique characteristics leading to solitary life, the challenges and problems which are faced by Sri Lankan Muslim minority, and the Islamic guidance from the thoughts and experience of prophetic school followed by the Muslim minority community in facing challenges and finding solutions. Also, the study analyzes the concept of dealing, the meaning of non-Muslims and their categories, the groups that the Prophet dealt with other communities during his time, and the principles for dealing with others in light of the Prophetic Tradition. The most important principles are right of nature, human dignity, compassion, equality, justice, freedom, and tolerance. These are considered the most important results of the study that also includes introducing the Shariah limitations and control for dealing of Sri Lankan Muslim minority by non-Muslim majority in certain important issues according to the constitution of Sri Lanka, its needs today, its citizen's attitude and their nature.